2008
DOI: 10.1016/j.jmwh.2008.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Low Maternal Awareness of Fetal Movement is Associated With Small for Gestational Age Infants

Abstract: Our aim was to identify associations between information given to pregnant women about fetal activity, level of maternal awareness of fetal activity, maternal concern about decreased fetal movement, and pregnancy outcomes. This was a population-based cross-sectional study. Mothers with a singleton delivery were invited to answer an anonymous structured questionnaire before discharge from the delivery unit. Six hundred and ninety-one mothers participated (60.4% of eligible women). Women were highly aware of fet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
63
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(68 citation statements)
references
References 48 publications
5
63
0
Order By: Relevance
“…This result is similar to a Norwegian study, where a third of participants did not recall receiving information about foetal movements. 13 Similar results have also been reported in New Zealand where 25% of women reported not receiving information 19 and recently in Canada where 34% of women did not recall receiving information. 20 The lack of information was reported to be higher in a developing country where 60% of South African women did not recall receiving information about foetal movements.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…This result is similar to a Norwegian study, where a third of participants did not recall receiving information about foetal movements. 13 Similar results have also been reported in New Zealand where 25% of women reported not receiving information 19 and recently in Canada where 34% of women did not recall receiving information. 20 The lack of information was reported to be higher in a developing country where 60% of South African women did not recall receiving information about foetal movements.…”
Section: Discussionsupporting
confidence: 75%
“…12,13 Some studies asked women about where or how they prefer to obtain their information, but not in relation to foetal activity specifically. 12,[14][15][16][17] The survey form included multiple choice options for sources of information and preferences, with some open ended questions to allow women to voice their opinions or make comments important to them.…”
Section: Survey Content and Developmentmentioning
confidence: 99%
“…13 Our statistical model allowed consideration of how duration affected perception within the context of other potential influences, that is, foetal body part moving and contact with maternal structures. This is an important finding, given that if the quantity or duration of foetal movement decreases, as occurs with a range of foetal complications 4,14,15 , mothers may report a decrease in the number of perceived movements. Mothers perceived a higher proportion of movements where the moving foetal part(s) contacted the uterus compared with those that only contacted the placenta or did not contact maternal structures.…”
Section: Discussionmentioning
confidence: 84%
“…This result agrees with Berndl et al, (2013) (24) and Saastad el al., (2008) (25) . While, Malm et al, (2014) (26) , indicated that low maternal awareness of fetal movements is associated with negative birth outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…ANZSA guidelines include giving all pregnant women advice about fetal movements, namely that it is normal to experience at least ten movements in 2 hours and advising women not to wait until the next day if they notice decreased or absent fetal movements (37) . Conversely, Saastad el al., (2008) (25) , concluded from their study that receiving information about expected fetal activity was associated with maternal concerns about decreased fetal movements, but not with improved outcomes.…”
Section: Discussionmentioning
confidence: 99%